JP-45/JSRP1 variants affect skeletal muscle excitation contraction coupling by decreasing the sensitivity of the dihydropyridine receptor - Yasuda, Toshimichi (2012)
JP-45 (also JP45; encoded by JSRP1) is an integral protein constituent of the skeletal muscle sarcoplasmic reticulum junctional face membrane interacting with Ca(v)1.1 (the α.1 subunit of the voltage sensing dihydropyridine receptor, DHPR) and the luminal calcium-binding protein calsequestrin. Two JSRP1 variants have been found in the human population: c.323C>T (p.P108L) in exon 5 and c.449G>C (p.G150A) in exon 6, but nothing is known concerning the incidence of these polymorphisms in the general population or in patients with neuromuscular diseases nor the impact of the polymorphisms on excitation-contraction coupling. In the present report we investigated the frequencies of these two JSRP1 polymorphisms in the Swiss Malignant Hyperthermia population and studied the functional impact of the variants on excitation -contraction coupling. Our results show that the polymorphisms are equally distributed among Malignant Hyperthermia Negative, Malignant Hyperthermia Equivocal and Malignant Hyperthermia Susceptible individuals. Interestingly however, the presence of either one of these JP-45 variants decreased the sensitivity of the dihydropyridine receptor to activation. The presence of a JSRP1 variant may explain the variable phenotype seen in patients with malignant hyperthermia carrying the same mutation and more importantly, may counteract the hypersensitivity of excitation-contraction coupling caused by mutations in the RYR1 gene.